EFEKTIVITAS LAYANAN PEDULI DILAN (DISABILITAS, ODGJ DAN LANSIA) DALAM MENINGKATKAN PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SIDOARJO - Rachmadhanty, Aulia; Meirinawati, Meirinawati (Publika, 2025)
Peduli Dilan service is an innovative program to improve accessibility of population administration services for people with with special needs in Sidoarjo Regency. This study aims to analyze the effectiveness of the Peduli Dilan service by using seven indicators of effectiveness according to Annas: timeliness, human resources that manage, work mechanisms, cooperation and communication, distribution of funds, no deviations, monitoring and evaluation. This research uses descriptive qualitative approach method with data collection techniques through interviews, observation and documentation. The results showed that in general In general, Peduli Dilan service has been running effectively. The service can be said run on time even though it does not have a fixed schedule due to limited officers, but officers have good competence in providing services. The service work mechanism runs according to the SOP and utilizing technological developments in the service process. Peduli Dilan service has collaborated and communicated with various stakeholders to support. In terms of fund distribution, operational funds sourced from the APBD which monitored through periodic evaluations and audits. In services, no irregularities were found and services were provided free of charge. Peduli Dilan service is routinely monitored and evaluated, but there is no specific SKM. To improve the effectiveness of services, it is recommended that there be an increase in the number of officers, as well as the preparation of a more specific a more specific community satisfaction survey (SKM) for service recipients.